Unpredictable maternal signals and developmental profiles of child executive function from infancy to early childhood - Takio, Fiia; Peura, Pilvi; Yada, Akie; Karonen, Anniina; Juntunen, Pauliina; Holmberg, Eeva; Eskola, Eeva; Nordenswan, Elisabeth; Deater-Deckard, Kirby; Kataja, Eeva-Leena; Tolvanen, Asko; Perasto, Laura; et al. (Elsevier BV, 2026)
Early executive function (EF) development is crucial for later cognitive and socioemotional outcomes, yet the role of environmental unpredictability, particularly in patterns of maternal sensory signals, remains underexplored. In this longitudinal study, we investigated the associations between unpredictability in maternal sensory signals and children’s early EF profiles from infancy through the preschool years. Using a population-based birth cohort, we observed a small but significant decrease in the unpredictability of maternal sensory signals over time. This suggests that caregiving predictability may increase as children develop. Nonetheless, within-individual unpredictability showed some stability across time. Importantly, lower unpredictability of maternal sensory signals was associated with membership in more favorable EF profiles, characterized by stronger working memory performance at age five. In contrast, children exposed to more unpredictable maternal sensory signals demonstrated poorer early EF development. These findings build on and extend prior work by modeling unpredictability of maternal sensory signals longitudinally beyond toddlerhood and linking it to children's EF development, highlighting the prolonged sensitivity of EFs to caregiving behavior. Our results underscore that unpredictability in caregiving behavior is a unique and critical factor in shaping early cognitive development and self-regulation. The findings align with emerging cross-species research indicating that patterns of sensory signals are vital not only for sensory processing but also for the development of higher-order cognitive functions. Together, these findings highlight the importance of addressing caregiving unpredictability in early interventions aimed at supporting children’s EF development.